Strength and conditioning for judo - Amtmann, J.; Cotton, A. (Strength and Conditioning Journal, 2005)
For elite judo athletes and recreational judo athletes alike, sportspecific strength and conditioning is essential in the prevention of injuries and for enhancing performance. This article offers suggestions for judo athletes and coaches for the development of strength and conditioning programs specific to the requirements of their sport.